Breaking the Mold: Non-Traditional Media for Teaching Political Science in Peru - Llanos Illescas, Luis Fernando (2025)
Political Science in Peru is often regarded as a subject in which students must focus on learning classical texts or theories that frequently bear little resemblance to the reality around them. However, in recent years, new trends have emerged—particularly through new instructors who seek to break away from traditional teaching approaches by introducing alternative media such as TV series, comics, or films. In this paper, we will examine the benefits and drawbacks of this approach through a review of the existing literature.